A brief history of living forever - Kalfar, Jaroslav (Little, Brown and Company, 2023)
In a 2030 America led by an isolationist authoritarian government, a star biotech scientist trying to discover the key to immortality becomes a whistleblower when she uncovers alarming activity in the wastelands of what was once Florida.